Towards a Taxonomy of Trustworthy Digital Repository Impacts. Issue 1 (13th October 2021) - Donaldson, Devan Ray; Russell, Samuel Vodicka
Abstract: Measuring the societal impact of digital repositories is a wicked problem. To capture information about the impacts of digital repositories that become certified as Trustworthy Digital Repositories (TDRs), a taxonomy describing activities cited as evidence of compliance with TDR standards is needed to relate those activities to socially beneficial outcomes. This paper presents a Minimum Viable Prototype (MVP) for a TDR Impacts taxonomy to enable the expression of their activities in a structured way. Our MVP provides a proof‐of‐concept that by formalizing concepts about TDRs in a taxonomy, we can investigate ways to measure whether the impacts associated with becoming and remaining a certified TDR are also impacts that generate societal value. Implications of the work described include potential strategies to identify, extract, and/or author machine‐readable descriptions of measurable facets of TDR activities and the resulting impacts on communities.